Incidencia del estrés laboral en el comportamiento del personal administrativo de la Universidad Politécnica Salesiana, campus El Girón. - Muñoz Oquendo, David Vinicio (2013)
The content of this thesis is an approach that emphasizes the stress concept, understood like a method that exists in the different planes of the life, of the subjects and characteristics that at the same time are positive and dangerous but it works for the health which is the activity that permits the development of the social life of the people. Subsequently, in this investigation we identify the relationship between health and work both in its positive or negative appearance. First of all we need to maintain the importance of the evolution of some concepts that have been used in all the work so in this way we can understand better the order of the investigation. Also the first part of this work will demonstrate that the purpose for this objective results will be a benefit for the institution.